Nondestructive Testing of Wood Defects Based on Stress Wave Technology - Wenshu Lin; Jinzhuo Wu (Institute of Advanced Engineering and Science, 2013)
The wood samples were tested by the technique of stress wave, and the testing results were analyzed by using the statistic software of SPSS. The results showed that the length, density and knots of wood, the sizes of holes and numbers of holes have significant influence on propagation parameters and dynamic modulus of elasticity. Under the same specifications, the propagation time of the stress wave was longer in the wood with holes than the perfect wood samples, and the time become longer with the increasing the sizes and numbers of holes. The studying results of this paper will provide a sound background for the application of stress-wave technique in detecting the inner defects of wood products and other wooden structures. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3532